Predicting Photocatalytic Properties of Metal Coupled Mn-TiO2 Particle Using Response Surface Methodology (RSM) as a Potential Filler in LED’s Encapsulant - Amna Jwad Kadem; Yin Xin Teo; Swee-Yong Pung; Srimala Sreekantan; Sivakumar Ramakrishnan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
This study addresses yellowing discoloration in LEDs caused by TiO2 particle degradation in encapsulants. The commonly added TiO2 particles will enhance light reflectance, and accelerate photodegradation but will decrease LED lifespan by lowering lumen quality and causing chromaticity change. To mitigate these effects, Mn particles were coupled with TiO2 particles using photo-reduction. This research examined three parameters Mn2+ ions concentration, UV irradiation duration, and annealing temperature, and the successful Mn-TiO2 coupling achieved. The resulting Mn-TiO2 particles, synthesized at 20 ppm Mn2+ ions and 200 °C annealing temperature, exhibited superior dispersibility and minimal agglomeration compared to TiO2 particles. Next, the photocatalytic performance of Mn-TiO2 particles was optimized using Response Surface Methodology (RSM). These particles exhibited the lowest photodegradation with a rate constant of 0.03092 min−1 and achieved a photodegradation efficiency of 79.92% at 60 min, amongst the others. Photodegradation of methylene blue followed a 1st-order kinetic model. Despite a slightly higher refractive index (RI), epoxy thin films with Mn-TiO2 particles displayed higher transmittance. Mn-TiO2 particles can thus serve as fillers in LED encapsulants to increase RI, reduce photodegradation, and enhance TiO2 particle dispersion. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).